Developmental control of glucocorticoid receptor transcriptional activity in embryonic retina. - Ben-Dror, I (1993)
In chicken embryo retina, competence for induction of the glutamine synthetase [L-glutamate:ammonia ligase (ADP-forming); EC 6.3.1.2] gene by glucocorticoid hormones increases progressively with development; this competence is minimal in 6-day retina (E6) and high by day 10 (E10). Because the level of glucocorticoid receptors (GRs) in the retina does not increase during that time, we investigated whether the transcriptional activity of GR increased between days 6 and 10 of development. The glucocorticoid-inducible chloramphenicol acetyltransferase (CAT) constructs 2GRE-37TK and p delta G46TCO, which contain glucocorticoid-responsive elements attached to a TATA box and to the thymidine kinase promoter, respectively, were transfected into E6 and E10 retinas, and their inducibility was examined. CAT expression could be induced in the transfected E10 retina but was not induced in the transfected E6 retina. However, induction was obtained also in E6 retina after cotransfection with a GR expression vector. Noninducible CAT constructs (pRSV-CAT, pSV2CAT, and pBLCAT2) were expressed at both ages at similar levels. The CAT construct pGS2.1CAT, which is controlled by the upstream sequence of the chicken glutamine synthetase gene, could be induced in E10 retina but was not induced in E6 retina; however, cotransfection with the GR expression vector resulted in induction of pGS2.1CAT also in E6 retina. We interpret these results as showing that the transcriptional activity of GR in embryonic retina is developmentally controlled and suggest that its increase is causally implicated in the development of competence for glutamine synthetase induction.